2014
DOI: 10.1186/s40557-014-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between shift work and hyperuricemia in steelmaking male workers

Abstract: ObjectivesThe aim of this study was to examine the association between shift work and hyperuricemia among steel company workers.MethodsWe examined 1,029 male workers at a Korean steel company between June 6 and June 28, 2013. We conducted anthropometric measurements, questionnaire surveys, and blood tests. Hyperuricemia was defined as a serum uric acid concentration of ≥7.0 mg/dL. Logistic regression analyses were performed. In the full model, analysis was adjusted for covariates including age, body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
2
6
0
3
Order By: Relevance
“…A late bedtime can increase circulating uric acid levels. There is a positive relationship between bedtime and urate levels in long-term shift workers, who have elevated urate levels (3,9). In this study, we found that patients with gout also had elevated urate levels.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A late bedtime can increase circulating uric acid levels. There is a positive relationship between bedtime and urate levels in long-term shift workers, who have elevated urate levels (3,9). In this study, we found that patients with gout also had elevated urate levels.…”
Section: Discussionsupporting
confidence: 48%
“…Sleep quality, duration, and bedtime are closely related to metabolic diseases such as hyperuricemia, diabetes, hypertension, and dyslipidaemia (4,5). For example, rotating shift workers often have elevated urate levels (6)(7)(8)(9). Qian (10) also found a signi cant association between bedtime and serum metabolites, such as uric acid and adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are few studies that determined the prevalence of hyperuricemia among workers in certain occupations. Oh et al,15 reported a significant positive association between shift work and hyperuricemia.…”
Section: Discussionmentioning
confidence: 98%
“…Given the close association between MetS and hyperuricemia, it is important to explore this relationship among workers as only few studies have reported the effects of occupational factors on plasma UA. Oh, et al,15 reported a significant association between shift work and hyperuricemia among Korean steelmaking male workers. In China, available evidence on the prevalence of hyperuricemia and its relationship with MetS focus on the general population16 or patients, with limited data on workers.…”
Section: Introductionmentioning
confidence: 99%
“…Tanto el SMet como otros factores de riesgo cardiovascular han sido estudiados en relación al trabajo a turnos, definido por la Organización Internacional del Trabajo (OIT) como "todo trabajo que se realice durante un período mínimo de siete horas consecutivas, que comprenda el intervalo entre medianoche y las cinco de la mañana y que será determinado por la autoridad competente previa consulta con las organizaciones empresariales y de trabajadores o por medio de convenios colectivos" (9) . Esta definición da pie a que diferentes instituciones a nivel nacional emitan las suyas propias (10,11,12) y a que puedan encontrarse multitud de éstas en las investigaciones (6,13) . Las distintas definiciones del trabajo a turnos, las características propias de los sectores profesionales que realizan turnos (por ejemplo, el sanitario frente al químico), los distintos tipos de turnos, la alternancia entre el trabajo diurno y nocturno, el sentido de rotación, un número bajo de años acumulados a turnos, así como las diferencias en los componentes que han de valorarse en el diagnóstico del SMet, hacen que las conclusiones de los estudios sean, a menudo, opuestas.…”
Section: Introductionunclassified